2018
DOI: 10.1021/acsbiomaterials.8b00198
|View full text |Cite
|
Sign up to set email alerts
|

Effective Wound Healing by Antibacterial and Bioactive Calcium-Fluoride-Containing Composite Hydrogel Dressings Prepared Using in Situ Precipitation

Abstract: In this study, we report the development of a hyaluronic acid (HA)-based composite hydrogel containing calcium fluoride (CaF2) with good biocompatibility and antibacterial properties for multifunctional wound dressing applications. CaF2 was newly selected for incorporation within HA because it can release both Ca2+ and F– ions, which are well-known ions for affecting cell proliferation and inhibiting bacterial growth, respectively. In particular, an in situ precipitation process enables easy control over the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…The rheological behaviors of the Alg and Alg-PDRN hydrogels were examined using a rheometer (ARES, Rheometric Scientific, USA) 52 , 53 . First, 1 ml of the hydrogels was placed between 20-mm-diameter parallel plates, and then, frequency sweep tests were performed under a constant strain of 0.5% in the frequency range of 1.0–100 rad/s.…”
Section: Methodsmentioning
confidence: 99%
“…The rheological behaviors of the Alg and Alg-PDRN hydrogels were examined using a rheometer (ARES, Rheometric Scientific, USA) 52 , 53 . First, 1 ml of the hydrogels was placed between 20-mm-diameter parallel plates, and then, frequency sweep tests were performed under a constant strain of 0.5% in the frequency range of 1.0–100 rad/s.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, the authors prepared chitosan/gelatin/nanocrystalline cellulose/calcium peroxide films for wound treatment application [ 73 ]. Calcium peroxide is an oxygen releasing biomaterial and has been found to possess antibacterial properties.…”
Section: Calcium-releasing Scaffoldsmentioning
confidence: 99%
“…However, no in vitro and in vivo wound healing experiments were conducted by the authors. Jeong et al used an in situ precipitation technique to produce calcium fluoride-containing composite hydrogel dressings and found that the presence of calcium fluoride enhanced the migration of fibroblasts and endothelial cells, and inhibited bacterial growth [ 73 ]. In vivo, a calcium fluoride composite hydrogel hastened wound healing by increasing the chemotaxis of immune cells, promoting the migration of surrounding skin cells, and accelerating the re-epithelialization process.…”
Section: Calcium-releasing Scaffoldsmentioning
confidence: 99%
“…Materials with bioactive properties for tissue engineering and long-term antibacterial properties are strongly desired for wound healing. Although many antibiotic-loaded dressings with excellent antibacterial properties have been developed, toxic effects, anaphylactic reactions and the resulting "super bacteria" that occurred due to drug resistance caused growing concern for finding new treatments [1][2][3]. In addition, various metalbased nanoparticles (NP), such as AgNP, ZnO NP and CeO 2 NP, with broad-spectrum antibacterial properties and without drug resistance are used as antibacterial agents in the study of wound dressings [4,5].…”
Section: Introductionmentioning
confidence: 99%